2010
DOI: 10.1099/mic.0.041723-0
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of caecal bacteria is altered in interleukin-10 gene-deficient mice before and after colitis onset and when fed polyunsaturated fatty acids

Abstract: Interleukin-10 gene-deficient (Il10 –/–) mice show a hyper-reaction to normal intestinal bacteria and develop spontaneous colitis similar to that of human Crohn's disease when raised under conventional (but not germ-free) conditions. The lack of IL10 protein in these mice leads to changes in intestinal metabolic and signalling processes. The first aim of this study was to identify changes in the bacterial community of the caeca at 7 weeks of age (preclinical colitis) and at 12 weeks of age (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Long-chain triglycerides can produce increased lymphocytes fluxes and enhanced proliferative response in intestinal lymph [36], whereas medium chain triglycerides can suppress IL-8, a neutrophil chemottractant expressed in high levels in actively inflamed mucosa of both CD and UC [37, 38]. Fats can also alter the microbiome [3941] that can lead to upregulation of TLR and NOD mediated inflammation [4244] and increased intestinal permeability from altered tight junction proteins [45, 46]. Milk derived saturated fats can alter the bile acid composition and allow for growth of sulfate-reducing bacteria such as Bilophila wadsworthia which produce toxic hydrogen sulfide and can aggravate colitis in IL10 knockout mouse models [4748].…”
Section: Macronutrient Associations With Ibdmentioning
confidence: 99%
“…Long-chain triglycerides can produce increased lymphocytes fluxes and enhanced proliferative response in intestinal lymph [36], whereas medium chain triglycerides can suppress IL-8, a neutrophil chemottractant expressed in high levels in actively inflamed mucosa of both CD and UC [37, 38]. Fats can also alter the microbiome [3941] that can lead to upregulation of TLR and NOD mediated inflammation [4244] and increased intestinal permeability from altered tight junction proteins [45, 46]. Milk derived saturated fats can alter the bile acid composition and allow for growth of sulfate-reducing bacteria such as Bilophila wadsworthia which produce toxic hydrogen sulfide and can aggravate colitis in IL10 knockout mouse models [4748].…”
Section: Macronutrient Associations With Ibdmentioning
confidence: 99%
“…86 Dietary PUFA altered diversity of cecal bacteria in mice 87 and IL-10-deficient mice. 88 In vitro and in vivo studies have shown that dietary fats increased small intestinal permeability through three mechanisms: 1) alteration of tight junction protein in rats 83,89 ; 2) modification of cellular membrane composition in T84 IEC 90 ; and 3) through AA-derived eicosanoids production. 91 In contrast, n-3 PUFA prevent this disruption of barrier function.…”
Section: Intestinal Barrier Function and Gut Microbiotamentioning
confidence: 99%
“…This suggests differences in intestinal bacteria that might be associated with the genotype which could contribute to the development of colitis in this mouse model (88).…”
Section: Mechanism Of Actionmentioning
confidence: 99%